2016
DOI: 10.1039/c6nj01532h
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted synthesis and photophysical studies of novel fluorescent N-acylhydrazone and semicarbazone-7-OH-coumarin dyes

Abstract: Emissive 7-OH-coumarins were synthesized by a microwave-assisted protocol and spectral changes were induced after conformational changes in low polarity media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…The electronic spectra of the compounds (SI, Figures S8 and S9) displayed intense spin–allowed π → π* absorption features around 450 nm in phosphate buffer, with ε on the order of 10 4 L mol –1 cm –1 . Coumarin derivatives containing the 7–N(Et) 2 and 7‐OH groups displayed absorptions around 350–430 nm, attributed to π → π* . Previous studies of coumarin–N–acylhydrazone hybrids and their corresponding Co III complexes showed the same type of transition in the region of 405–470 nm in phosphate buffer.…”
Section: Resultsmentioning
confidence: 68%
“…The electronic spectra of the compounds (SI, Figures S8 and S9) displayed intense spin–allowed π → π* absorption features around 450 nm in phosphate buffer, with ε on the order of 10 4 L mol –1 cm –1 . Coumarin derivatives containing the 7–N(Et) 2 and 7‐OH groups displayed absorptions around 350–430 nm, attributed to π → π* . Previous studies of coumarin–N–acylhydrazone hybrids and their corresponding Co III complexes showed the same type of transition in the region of 405–470 nm in phosphate buffer.…”
Section: Resultsmentioning
confidence: 68%
“…Electronic spectral data for Hachbt and its complexes ( 1 – 5 ) in DMSO are listed in the Experimental section and are shown in Figure S3. The ligand exhibits three bands at 289, 365 and 546 nm due to intraligand π‐π* and n‐π* transitions 64, 65 . The UV–Vis spectra of the Zn (II) and Ag (1) complexes (d 10 configuration) show similar behavior to that of the ligand with slight red shifts to the higher wavelengths (~ 5 nm) owing to coordination to the metal ion 52, 66 .…”
Section: Resultsmentioning
confidence: 97%
“…In the mid-nineteenth century, the research and development of coumarin-based compounds and hybrid structures began via the famous Perkin condensation reaction between acetic anhydride and salicylaldehyde. The different synthetic classical techniques, such as Knoevenagel, Perkin and Pechmann reactions, are applied to achieve simple coumarins [ 5 , 6 , 7 ]. The rapid developments in the synthetic chemistry of coumarins have been made, due to their wide therapeutic potential as medicinal drugs.…”
Section: Introductionmentioning
confidence: 99%